1981
DOI: 10.1002/esp.3290060102
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of sandstone by the combined action of frost and salt

Abstract: Preliminary results from a continuing series of laboratory experiments designed to examine the combined effects of salt and frost weathering indicate that some salts greatly enhance the breakdown of rocks by frost. Samples of Ardingly Sandstone from southeast England were soaked in saturated solutions of sodium chloride or sodium sulphate and subjected to alternating cycles of freezing and thawing. Rapid disintegration of the sandstone occurred within twenty cycles, in each of the salt solutions. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 2 publications
1
41
0
Order By: Relevance
“…The possibility that salt weathering is enhanced in conjunction with frost has been discussed by previous authors (Williams and Robinson, 1981;McGreevey, 1982;Robinson and Jerwood, 1987a, b). Fahey (1983) has demonstrated that hydration weathering of schist is enhanced by frost.…”
Section: Discussionmentioning
confidence: 91%
“…The possibility that salt weathering is enhanced in conjunction with frost has been discussed by previous authors (Williams and Robinson, 1981;McGreevey, 1982;Robinson and Jerwood, 1987a, b). Fahey (1983) has demonstrated that hydration weathering of schist is enhanced by frost.…”
Section: Discussionmentioning
confidence: 91%
“…Williams and Robinson, 1981). It occurs with or without the addition of salts, presumably because the pores are being enlarged slightly by frost action, allowing more solution to be absorbed.…”
Section: Discussionmentioning
confidence: 98%
“…Experiments by Dunn and Hudec (1966) and Goudie (1974) demonstrated that salts could enhance the frost weathering of calcareous rocks, and Williams and Robinson (1981) showed that frost weathering of sandstone was greatly enhanced by the presence of sodium sulphate or sodium chloride. The range of possible mechanisms by which salts may enhance frost weathering have been discussed by Williams and Robinson (1991).…”
Section: Introductionmentioning
confidence: 97%
“…Ice and salt crystal growth can have strongly disruptive effects on weak, fractured rock, and the surfaces and subsurface layers show weathering patterns of the kinds typically associated with frost and salt action on sandstone (Figures 2 and 3). Williams and Robinson ( 1983) found the highly porous Ardingly sandstone readily disintegrated during freeze-thaw cycles following saturation in various salt solutions. Strong variations in weathering reflected differences in grain size with samples having high silt/clay contents being most susceptible.…”
Section: Study Areamentioning
confidence: 99%